South-South cooperation in education and development: The ¡Yo, Sí Puedo! literacy method - Muhr, Thomas (Elsevier, 2015)
This article addresses two tendencies within the international education and South–South cooperation literatures: the omission of the Bolivarian Alliance for the Peoples of Our America-Peoples’ Trade Agreement (ALBA-TCP) from discussions of South–South cooperation generally, and of the ALBATCP promoted ¡Yo, Sí Puedo! literacy method in particular. Central features of ¡Yo, Sí Puedo! are discussed, while the case of ¡Yo, Sí Puedo! in Nicaragua illustrates the main argument developed: ¡Yo, Sí Puedo! should not be regarded as ‘best practice transfer’ but as integral to South–South cooperation as Third World emancipation and transformation towards a socially just and democratic world order.